Acrylic rubber composition and crosslinked rubber

By using specific types of carbon black and plasticizers in acrylic rubber compositions, the lack of acrylic rubber compositions in existing technologies in roller processing, cold resistance, and stretch strength have achieved better performance.

CN119384461APending Publication Date: 2025-01-28ZEON CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380051599.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-29
Filing Date
2023-07-26
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

In the prior art, there is room for improvement in the acrylic rubber composition in terms of roll processability, cold resistance and tensile strength.

Method used

By using a carbonic acid rubber composition with a nitrogen adsorption ratio/iodine adsorption of 1.00 × 103m2/g and above the nitrogen adsorption ratio of 25m2/g, a nitrogen adsorption ratio of 25m2/g, combined with an appropriate amount of plasticizer, optimized the composition of the composition to so as to use Improve its roller processing and performance.

Benefits of technology

The roller processing of acrylic rubber composition is achieved, and rubber cross -linked objects with excellent cold resistance and stretch strength have been formed.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present invention provides an acrylic rubber composition containing: an acrylic rubber having a glass transition temperature of-29 DEG C or less; and carbon black having a nitrogen adsorption specific surface area / iodine adsorption amount of 1.00 * 103 m2 / g or more and a nitrogen adsorption specific surface area of 25 m2 / g or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an acrylic rubber composition which is excellent in roll processability and can form a rubber cross-linked product having excellent cold resistance and tensile strength, and a rubber cross-linked product. Background Art

[0002] Hitherto, rubber products imparted with various properties have been developed according to the application. For example, Patent Document 1 discloses an acrylic rubber composition for a heat-resistant hose.

[0003] Patent Document 1 discloses a heat-resistant hose acrylic rubber composition containing carbon black and having high electrical resistance and high strength. However, there is room for improvement in roll processability, cold resistance and tensile strength of a rubber cross-linked product obtained from the acrylic rubber composition.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent document 1: Japanese Patent Application Publication No. 2016-150525. Summary of the invention

[0007] Problem that the invention aims to solve

[0008] The present invention has been made in view of such actual circumstances, and an object of the present invention is to provide a rubber composition having excellent roll processability and capable of forming a rubber cross-linked product having excellent cold resistance and tensile strength, and a rubber cross-linked product obtained by cross-linking such a rubber composition.

[0009] Solutions for solving problems

[0010] The inventors of the present invention have conducted intensive research and found that by containing a nitrogen adsorption specific surface area / iodine adsorption amount of 1.00×10 3 m 2 / g or more and the nitrogen adsorption specific surface area is 25m 2 The present invention has been completed by achieving the above-mentioned object through the acrylic rubber composition containing carbon black of 0.1% to 0.1% by weight and 0.1% to 0.1% by weight.

[0011] That is, according to the first embodiment of the present invention, there is provided an acrylic rubber composition comprising: an acrylic rubber having a glass transition temperature of −29° C. or lower; and carbon black having a nitrogen adsorption specific surface area / iodine adsorption amount of 1.00×10 3 m 2 / g or more and the nitrogen adsorption specific surface area is 25m 2 / g or above.

[0012] According to a second aspect of the present invention, there is provided an acrylic rubber composition comprising: an acrylic rubber; and carbon black having a nitrogen adsorption specific surface area / iodine adsorption amount of 1.00×10 3 m 2 / g or more and the nitrogen adsorption specific surface area is 25m 2 / g or more; and a plasticizer; the content of the plasticizer is 3 parts by weight or more relative to 100 parts by weight of the rubber component containing the acrylic rubber.

[0013] According to a third aspect of the present invention, there is provided the acrylic rubber composition of the first aspect, wherein the acrylic rubber composition further contains a plasticizer.

[0014] According to a fourth aspect of the present invention, there is provided an acrylic rubber composition according to any one of aspects 1 to 3, wherein the carbon black has a nitrogen adsorption specific surface area of ​​25 to 60 m 2 / g, the nitrogen adsorption specific surface area / iodine adsorption of the above carbon black is 1.10×10 3 ~1.50×10 3 m 2 / g.

[0015] According to a fifth aspect of the present invention, there is provided the acrylic rubber composition according to any one of aspects 1 to 4, wherein the carbon black has a DBP absorption of 90 to 180 cm 3 / 100g.

[0016] According to mode 6 of the present invention, there is provided an acrylic rubber composition of any one of modes 1 to 5, wherein in the above-mentioned carbon black, when a nuclear magnetic resonance signal of a spin-spin relaxation process observed by a solid echo method is represented by a sum of a first signal and a second signal having a time constant greater than that of the above-mentioned first signal, the amount of hydrogen represented by the signal intensity per unit mass of the above-mentioned first signal at time 0 is 150 to 250 / g.

[0017] According to a seventh aspect of the present invention, there is provided an acrylic rubber composition according to any one of aspects 1 to 6, wherein in the carbon black, at an excitation wavelength of 532 nm, the carbon black has a molecular weight of 1.340 to 1.360 cm -1 The half-peak width ΔD of the Raman scattering peak in the range of 260 to 290 cm -1 .

[0018] According to an eighth aspect of the present invention, there is provided the acrylic rubber composition of the first or second aspect, wherein the carbon black has a nitrogen adsorption specific surface area of ​​25 to 60 m 2 / g, the nitrogen adsorption specific surface area / iodine adsorption of the above carbon black is 1.10×10 3 ~1.50×10 3 m 2 / g, the DBP absorption of the above carbon black is 90 to 180 cm 3 / 100g, in the above carbon black, when the nuclear magnetic resonance signal of the spin-spin relaxation process observed by the solid echo method is represented by the sum of a first signal and a second signal having a time constant greater than that of the above first signal, the amount of hydrogen represented by the signal intensity per unit mass at time 0 of the above first signal is 150 to 250 / g, and in the above carbon black, when the excitation wavelength is set to 532nm, the hydrogen content in the range of 1340 to 1360cm -1 The half-peak width ΔD of the Raman scattering peak in the range of 260 to 290 cm -1 .

[0019] According to a ninth aspect of the present invention, there is provided a cross-linked rubber product obtained by cross-linking the acrylic rubber composition according to any one of the first to eighth aspects with an amine compound.

[0020] Effects of the Invention

[0021] According to the present invention, there can be provided an acrylic rubber composition having excellent roll processability and capable of forming a rubber cross-linked product having excellent cold resistance and tensile strength, and a rubber cross-linked product obtained by cross-linking such an acrylic rubber composition. DETAILED DESCRIPTION

[0022] <<First embodiment>>

[0023] The acrylic rubber composition in the first embodiment of the present invention comprises: an acrylic rubber having a glass transition temperature of -29°C or lower; and carbon black having a nitrogen adsorption specific surface area / iodine adsorption amount of 1.00×10 3 m 2 / g or more and the nitrogen adsorption specific surface area is 25m 2 / g or above.

[0024] <Acrylic rubber>

[0025] The acrylic rubber used in the present invention is a rubbery polymer containing a (meth)acrylate monomer [meaning an acrylate monomer and / or a methacrylate monomer; hereinafter, the same shall apply to (meth)acrylic acid methyl] unit as a main component (meaning a component preferably accounting for 30% by weight or more of all monomer units constituting the acrylic rubber) in the molecule.

[0026] The (meth)acrylic acid ester monomer forming the (meth)acrylic acid ester monomer unit which is the main component of the acrylic rubber used in the present invention is not particularly limited, and examples thereof include alkyl (meth)acrylic acid ester monomers and alkoxyalkyl (meth)acrylic acid ester monomers.

[0027] The (meth)acrylic acid alkyl ester monomer is not particularly limited, but is preferably an ester of an alkanol having 1 to 12 carbon atoms and (meth)acrylic acid (a (meth)acrylic acid ester having an alkyl group having 1 to 12 carbon atoms), more preferably an ester of an alkanol having 1 to 8 carbon atoms and (meth)acrylic acid (a (meth)acrylic acid ester having an alkyl group having 1 to 8 carbon atoms), and still more preferably an ester of an alkanol having 2 to 6 carbon atoms and (meth)acrylic acid (a (meth)acrylic acid ester having an alkyl group having 2 to 6 carbon atoms).

[0028] Specific examples of the (meth)acrylic acid alkyl ester monomer include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, n-hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and cyclohexyl (meth)acrylate. Among these, ethyl (meth)acrylate and n-butyl (meth)acrylate are preferred, and ethyl acrylate and n-butyl acrylate are more preferred. These can be used alone or in combination of two or more.

[0029] The alkoxyalkyl (meth)acrylate monomer is not particularly limited, but is preferably an ester of an alkoxyalkyl alcohol having 2 to 12 carbon atoms and (meth)acrylic acid (a (meth)acrylate having an alkoxyalkyl group having 2 to 12 carbon atoms), more preferably an ester of an alkoxyalkyl alcohol having 2 to 8 carbon atoms and (meth)acrylic acid (a (meth)acrylate having an alkoxyalkyl group having 2 to 8 carbon atoms), and still more preferably an ester of an alkoxyalkyl alcohol having 2 to 6 carbon atoms and (meth)acrylic acid (a (meth)acrylate having an alkoxyalkyl group having 2 to 6 carbon atoms).

[0030] Specific examples of the (meth) alkoxyalkyl ester monomer include methoxymethyl (meth) acrylate, ethoxymethyl (meth) acrylate, 2-methoxyethyl (meth) acrylate, 2-ethoxyethyl (meth) acrylate, 2-propoxyethyl (meth) acrylate, 2-butoxyethyl (meth) acrylate, 3-methoxypropyl (meth) acrylate, and 4-methoxybutyl (meth) acrylate. Among these, 2-ethoxyethyl (meth) acrylate and 2-methoxyethyl (meth) acrylate are preferred, and 2-ethoxyethyl acrylate and 2-methoxyethyl acrylate are particularly preferred. These can be used alone or in combination of two or more.

[0031] The content of the (meth)acrylate monomer unit in all monomer units constituting the acrylic rubber used in the present invention is preferably 50% by weight or more, more preferably 60% by weight or more, further preferably 70 to 99.9% by weight, further preferably 80 to 99.5% by weight, and particularly preferably 90 to 99% by weight. If the content of the (meth)acrylate monomer unit is too low, the weather resistance, heat resistance, and oil resistance of the obtained rubber cross-linked product may be reduced.

[0032] In addition, the acrylic rubber used in the present invention preferably contains at least a (meth) acrylate alkoxyalkyl ester monomer unit as a (meth) acrylate monomer unit. By containing the (meth) acrylate alkoxyalkyl ester monomer unit, the obtained rubber cross-linked product can have excellent cold resistance and engine oil resistance. In addition, by making the acrylic rubber contain a (meth) acrylate alkoxyalkyl ester monomer unit, the inhibitory effect of coloration and odor can be further improved. The content of the (meth) acrylate alkoxyalkyl ester monomer unit in all the monomer units constituting the acrylic rubber used in the present invention is preferably 1 to 70% by weight, more preferably 1 to 60% by weight, further preferably 5 to 60% by weight, and particularly preferably 5 to 50% by weight.

[0033] The acrylic rubber used in the present invention may contain crosslinking monomer units in addition to (meth)acrylate monomer units as required. The crosslinking monomers forming the crosslinking monomer units are not particularly limited, and examples thereof include monomers having reactive polar functional groups such as α, β-ethylenically unsaturated carboxylic acid monomers, monomers having epoxy groups, monomers having halogen atoms, and diene monomers. As crosslinking monomers, from the viewpoint of crosslinking properties, monomers having reactive polar functional groups are preferred. Among monomers having reactive polar functional groups, α, β-ethylenically unsaturated carboxylic acid monomers, monomers having epoxy groups, and monomers having halogen atoms are more preferred. α, β-ethylenically unsaturated carboxylic acid monomers and monomers having halogen atoms are further preferred, and α, β-ethylenically unsaturated carboxylic acid monomers and monomers having halogen atoms are particularly preferred. α, β-ethylenically unsaturated carboxylic acid monomers are particularly preferred.

[0034] The α,β-ethylenically unsaturated carboxylic acid monomer is not particularly limited, and examples thereof include α,β-ethylenically unsaturated monocarboxylic acids, α,β-ethylenically unsaturated dicarboxylic acids, and α,β-ethylenically unsaturated dicarboxylic acid monoesters. By using the α,β-ethylenically unsaturated carboxylic acid monomer, the acrylic rubber can be made into a carboxyl group-containing acrylic rubber having a carboxyl group as a crosslinking point, thereby further improving the compression set resistance when the rubber crosslinked product is prepared.

[0035] The α,β-ethylenically unsaturated monocarboxylic acid is not particularly limited, but is preferably an α,β-ethylenically unsaturated monocarboxylic acid having 3 to 12 carbon atoms. Specific examples thereof include acrylic acid, methacrylic acid, α-ethylacrylic acid, crotonic acid, and cinnamic acid.

[0036] The α,β-ethylenically unsaturated dicarboxylic acid is not particularly limited, but is preferably an α,β-ethylenically unsaturated dicarboxylic acid having 4 to 12 carbon atoms. Specific examples thereof include butenedioic acids such as fumaric acid and maleic acid; itaconic acid; citraconic acid; and chloromaleic acid.

[0037] The α,β-ethylenically unsaturated dicarboxylic acid monoester is not particularly limited, but is preferably a monoester of an α,β-ethylenically unsaturated dicarboxylic acid having 4 to 12 carbon atoms and an alkanol having 1 to 12 carbon atoms, more preferably a monoester of an α,β-ethylenically unsaturated dicarboxylic acid having 4 to 6 carbon atoms and an alkanol having 2 to 8 carbon atoms, and still more preferably a monoester of butenedioic acid having 4 carbon atoms and an alkanol having 2 to 6 carbon atoms. Specific examples of α,β-ethylenically unsaturated dicarboxylic acid monoesters include: monomethyl fumarate, monoethyl fumarate, mono-n-butyl fumarate, monomethyl maleate, monoethyl maleate, mono-n-butyl maleate and other single-chain alkyl esters of butenedioic acid; monocyclopentyl fumarate, monocyclohexyl fumarate, monocyclohexenyl fumarate, monocyclopentyl maleate, monocyclohexyl maleate, monocyclohexenyl maleate and other butenedioic acid monoesters having an alicyclic structure; monomethyl itaconate, monoethyl itaconate, mono-n-butyl itaconate, monocyclohexyl itaconate and other itaconic acid monoesters; and the like.

[0038] Among these, α,β-ethylenically unsaturated dicarboxylic acid monoesters are preferred, butenedioic acid single-chain alkyl esters or butenedioic acid monoesters with alicyclic structures are more preferred, fumaric acid mono-n-butyl ester, maleic acid mono-n-butyl ester, fumaric acid mono-cyclohexyl ester and maleic acid mono-cyclohexyl ester are further preferred, and fumaric acid mono-n-butyl ester is particularly preferred. These α,β-ethylenically unsaturated carboxylic acid monomers can be used alone or in combination of two or more. In addition, among the above-mentioned monomers, dicarboxylic acids also include dicarboxylic acids in the form of anhydrides.

[0039] The monomer having an epoxy group is not particularly limited, and examples thereof include epoxy group-containing (meth)acrylates such as glycidyl (meth)acrylate; and epoxy group-containing ethers such as allyl glycidyl ether and vinyl glycidyl ether.

[0040] The monomer having a halogen atom is not particularly limited, and examples thereof include unsaturated alcohol esters of halogen-containing saturated carboxylic acids, halogenated alkyl (meth)acrylates, halogenated acyloxyalkyl (meth)acrylates, (halogenated acetylcarbamoyloxy)alkyl (meth)acrylates, halogen-containing unsaturated ethers, halogen-containing unsaturated ketones, halogenated methyl-containing aromatic vinyl compounds, halogen-containing unsaturated amides, and halogenated acetyl-containing unsaturated monomers. In addition, as the monomer having a halogen atom, a monomer containing a chlorine atom as the halogen atom is preferred.

[0041] Specific examples of the unsaturated alcohol ester of a halogen-containing saturated carboxylic acid include vinyl chloroacetate, vinyl 2-chloropropionate, and allyl chloroacetate.

[0042] Specific examples of the haloalkyl (meth)acrylate include chloromethyl (meth)acrylate, 1-chloroethyl (meth)acrylate, 2-chloroethyl (meth)acrylate, 1,2-dichloroethyl (meth)acrylate, 2-chloropropyl (meth)acrylate, 3-chloropropyl (meth)acrylate, and 2,3-dichloropropyl (meth)acrylate.

[0043] Specific examples of the haloacyloxyalkyl (meth)acrylate include 2-(chloroacetoxy)ethyl (meth)acrylate, 2-(chloroacetoxy)propyl (meth)acrylate, 3-(chloroacetoxy)propyl (meth)acrylate, and 3-(hydroxychloroacetoxy)propyl (meth)acrylate.

[0044] Specific examples of the (haloacetylcarbamoyloxy)alkyl (meth)acrylate include 2-(chloroacetylcarbamoyloxy)ethyl (meth)acrylate and 3-(chloroacetylcarbamoyloxy)propyl (meth)acrylate.

[0045] Specific examples of the halogen-containing unsaturated ether include chloromethyl vinyl ether, 2-chloroethyl vinyl ether, 3-chloropropyl vinyl ether, 2-chloroethyl allyl ether, and 3-chloropropyl allyl ether.

[0046] Specific examples of the halogen-containing unsaturated ketone include 2-chloroethyl vinyl ketone, 3-chloropropyl vinyl ketone, and 2-chloroethyl allyl ketone.

[0047] Specific examples of the halogenated methyl group-containing aromatic vinyl compound include p-chloromethylstyrene, m-chloromethylstyrene, o-chloromethylstyrene, and p-chloromethyl-α-methylstyrene.

[0048] Specific examples of the halogen-containing unsaturated amide include N-chloromethyl (meth) acrylamide and the like.

[0049] Specific examples of the halogenated acetyl group-containing unsaturated monomer include 3-(hydroxychloroacetyloxy)propyl allyl ether and p-vinylbenzyl chloroacetate.

[0050] Examples of the diene monomer include conjugated diene monomers and non-conjugated diene monomers.

[0051] Specific examples of the conjugated diene monomer include 1,3-butadiene, isoprene, and piperylene.

[0052] Specific examples of the non-conjugated diene monomer include ethylidene norbornene, dicyclopentadiene, dicyclopentadienyl (meth)acrylate, and 2-dicyclopentadienylethyl (meth)acrylate.

[0053] The content of the crosslinkable monomer unit in all monomer units constituting the acrylic rubber used in the present invention is preferably 0.01% by weight or more, more preferably 0.01 to 20% by weight, further preferably 0.1 to 10% by weight, further preferably 0.5 to 5% by weight, and particularly preferably 1 to 3% by weight. By making the content of the crosslinkable monomer unit within the above range, the mechanical properties and heat resistance of the obtained rubber cross-linked product can be improved while the compression set resistance can be more appropriately improved.

[0054] In addition, the acrylic rubber used in the present invention may have units of other monomers copolymerizable with the above monomer units in addition to the (meth)acrylate monomer units and the crosslinking monomer units used as needed. Such other monomers copolymerizable are not particularly limited, and examples thereof include aromatic vinyl monomers, α,β-ethylenically unsaturated nitrile monomers, acrylamide monomers, α,β-ethylenically unsaturated dicarboxylic acid diester monomers, and other olefin monomers.

[0055] Examples of the aromatic vinyl monomer include styrene, α-methylstyrene, and divinylbenzene.

[0056] Examples of the α,β-ethylenically unsaturated nitrile monomer include acrylonitrile and methacrylonitrile.

[0057] Examples of the acrylamide-based monomer include acrylamide and methacrylamide.

[0058] Examples of the α,β-ethylenically unsaturated dicarboxylic acid diester monomer include: dialkyl maleates having an alkyl group with 1 to 18 carbon atoms, such as dimethyl maleate and di-n-butyl maleate; dialkyl fumarates having an alkyl group with 1 to 18 carbon atoms, such as dimethyl fumarate and di-n-butyl fumarate; dicycloalkyl maleates having a cycloalkyl group with 4 to 16 carbon atoms, such as dicyclopentyl maleate and dicyclohexyl maleate; dicycloalkyl fumarates having a cycloalkyl group with 4 to 16 carbon atoms, such as dicyclopentyl fumarate and dicyclohexyl fumarate; dialkyl itaconates having an alkyl group with 1 to 18 carbon atoms, such as dimethyl itaconate and di-n-butyl itaconate; and dicycloalkyl itaconates having a cycloalkyl group with 4 to 16 carbon atoms, such as dicyclohexyl itaconate.

[0059] Examples of other olefin monomers include ethylene, propylene, vinyl chloride, vinylidene chloride, vinyl acetate, ethyl vinyl ether, and butyl vinyl ether.

[0060] Among these other copolymerizable monomers, styrene, acrylonitrile, methacrylonitrile, ethylene and vinyl acetate are preferred, and acrylonitrile, methacrylonitrile and ethylene are more preferred.

[0061] The other copolymerizable monomers can be used alone or in combination of two or more. The content of the units of the other copolymerizable monomers in the acrylic rubber monomer units used in the present invention is preferably 49.9 wt % or less, more preferably 29.9 wt % or less, further preferably 15 wt % or less, further preferably 9 wt % or less, and particularly preferably 4.5 wt % or less.

[0062] In addition, when the acrylic rubber used in the present invention contains units capable of copolymerizing other monomers, the content thereof may be within the above range, and when the acrylic rubber contains ethylene units, the content of the ethylene units in the monomer units constituting the acrylic rubber used in the present invention is preferably 9% by weight or less, and more preferably 4.5% by weight or less. Similarly, when the acrylic rubber used in the present invention contains acrylonitrile units and methacrylonitrile units, the total content of the acrylonitrile units and methacrylonitrile units is preferably 9% by weight or less, and more preferably 4.5% by weight or less.

[0063] The acrylic rubber used in the present invention can be obtained by polymerizing the above-mentioned monomers. As the polymerization reaction method, any one of emulsion polymerization, suspension polymerization, bulk polymerization and solution polymerization can be used. From the aspects of the ease of control of the polymerization reaction, the method based on emulsion polymerization under normal pressure, which is commonly used as a method for producing acrylic rubber known in the past, is preferred.

[0064] Emulsion polymerization can be any of batch, semi-batch, and continuous. Polymerization is usually carried out at a temperature range of 0 to 70°C, preferably 5 to 50°C. The above-mentioned monomers do not have to be supplied to the reaction site in all types and amounts from the beginning of the reaction. They can be added continuously or intermittently during the entire reaction time, or introduced once or in batches in the middle or even in the second half, taking into account the copolymerization reactivity ratio, reaction conversion rate, etc. In addition, the feed ratio of each of the above-mentioned monomers in the polymerization reaction can be adjusted according to the reactivity of each monomer, but the polymerization reaction is mostly carried out roughly quantitatively. Therefore, considering such a situation, the feed ratio can be determined according to the monomer unit composition of the acrylic rubber to be manufactured. After polymerization, solid acrylic rubber is obtained by coagulation and drying.

[0065] The glass transition temperature (Tg) of the acrylic rubber used in the present invention is -29°C or lower, preferably -30°C or lower, and more preferably -32°C or lower. The lower limit of the glass transition temperature of the acrylic rubber is not particularly limited, but is preferably -80°C or higher, preferably -60°C or higher, and more preferably -40°C or higher. By setting the glass transition temperature (Tg) within the above range, the balance between heat resistance and cold resistance of the acrylic rubber can be made more excellent.

[0066] The acrylic rubber used in the present invention may contain a phenolic antioxidant as an antioxidant. As the phenolic antioxidant, any compound having a phenol structure (i.e., a structure having a benzene ring and an OH group bonded to the benzene ring) is not particularly limited. As the phenolic antioxidant, for example, a double hindered phenolic antioxidant, a semi-hindered phenolic antioxidant, a low hindered phenolic antioxidant, a phenolic antioxidant having no hindered group, etc. may be cited.

[0067] The pH of the acrylic rubber used in the present invention is not particularly limited, but is preferably 6 or less, more preferably 2 to 6, further preferably 2.5 to 5.5, and particularly preferably 3 to 5. By setting the pH within the above range, the storage stability of the acrylic rubber composition can be further improved.

[0068] The weight average molecular weight (Mw) of the acrylic rubber contained in the acrylic rubber composition of the present invention is not particularly limited, but is preferably 800,000 or more, more preferably 800,000 to 2,600,000, further preferably 900,000 to 2,300,000, and particularly preferably 1,000,000 to 2,000,000. The molecular weight distribution of the acrylic rubber is not particularly limited, but is preferably 1.50 to 10.0, more preferably 1.70 to 8.00, and further preferably 2.00 to 6.00 in terms of Mw / Mn, and is preferably 1.30 to 3.00, more preferably 1.45 to 2.70, and further preferably 1.60 to 2.50 in terms of Mz / Mw. The weight average molecular weight and molecular weight distribution of the acrylic rubber can be determined as absolute molecular weight and absolute molecular weight distribution by, for example, a GPC-MALS method using a GPC (Gel Permeation Chromatography) apparatus equipped with a multi-angle laser light scattering photometer (MALS).

[0069] <Acrylic rubber composition>

[0070] The acrylic rubber composition of the present invention comprises: a rubber component comprising the acrylic rubber; and carbon black having a nitrogen adsorption specific surface area / iodine adsorption amount of 1.00×10 3 m 2 / g or more and the nitrogen adsorption specific surface area is 25m 2 / g or above.

[0071] The ratio of the acrylic rubber component in the rubber component of the acrylic rubber composition may be appropriately selected depending on the intended use, and is preferably 30% by weight or more, more preferably 50% by weight or more, further preferably 70% by weight or more, and particularly preferably 100% by weight (i.e., an embodiment in which a rubber consisting essentially of only the acrylic rubber component is used as the rubber component).

[0072] The rubber other than acrylic rubber used in the present invention constituting the rubber component is not particularly limited, and examples thereof include acrylic rubber other than acrylic rubber used in the present invention, natural rubber, polybutadiene rubber, polyisoprene rubber, styrene-butadiene rubber, acrylonitrile-butadiene rubber, silicone rubber, fluororubber, olefin elastomer, styrene elastomer, vinyl chloride elastomer, polyester elastomer, polyamide elastomer, polyurethane elastomer, polysiloxane elastomer, and the like.

[0073] The rubber other than acrylic rubber can be used alone or in combination of two or more. The shape of the acrylic rubber used in the present invention and the shape of the rubber other than acrylic rubber used in the present invention are not particularly limited and may be in any of the following shapes: bag, sheet, powder, etc.

[0074] The nitrogen adsorption specific surface area / iodine adsorption amount of the carbon black used in the present invention is 1.00×10 3 m 2 / g or more, preferably 1.10×10 3 m 2 / g or more, more preferably 1.20×10 3 m 2 / g or more, particularly preferably 1.30×10 3 m 2 The upper limit of the nitrogen adsorption specific surface area / iodine adsorption amount of carbon black is not particularly limited, but is preferably 1.50×10 3 m 2 / g or less, more preferably 1.40×10 3 m 2 / g or less. Nitrogen adsorption specific surface area / iodine adsorption amount represents the surface activity of carbon black. By making the nitrogen adsorption specific surface area / iodine adsorption amount of carbon black within the above range, the roll processability of the acrylic rubber composition can be improved, and the tensile strength of the obtained rubber cross-linked product can be improved.

[0075] The nitrogen adsorption specific surface area of ​​carbon black is 25m 2 / g or more, preferably 35m 2 / g or more, more preferably 45m 2The upper limit of the nitrogen adsorption specific surface area of ​​carbon black is not particularly limited, but is preferably 60 m 2 / g or less, more preferably 55m 2 The nitrogen adsorption specific surface area of ​​carbon black can be measured in accordance with JIS K6217-7:2013.

[0076] The iodine adsorption of carbon black is preferably 60 mg / g or less, more preferably 50 mg / g or less. The lower limit of the iodine adsorption of carbon black is not particularly limited, but is preferably 17 mg / g or more, more preferably 30 mg / g or more. The iodine adsorption of carbon black can be measured according to JIS K6217-1997.

[0077] The DBP absorption of carbon black is preferably 90 to 180 cm 3 / 100g, more preferably 115 to 135cm 3 / 100g. The DBP absorption indicates the structure (degree of agglomeration) of carbon black and can be measured in accordance with JIS K6217-1997. By making the DBP absorption within the above range, the roll processability of the acrylic rubber composition can be excellent, and the tensile strength of the obtained rubber cross-linked product can be excellent.

[0078] The amount of hydrogen in carbon black as determined by a nuclear magnetic resonance apparatus (NMR) is preferably 150 to 250 / g. When the amount of hydrogen in carbon black is within the above range, the dispersibility of carbon black is improved, and the tensile strength of the obtained rubber cross-linked product can be made excellent.

[0079] The amount of hydrogen in carbon black can be determined by the following method. First, using Minispecmq20 from Bruker Co., Ltd. as a pulsed magnetic resonance apparatus, the carbon black is dried at 110°C for 30 minutes, and then 0.2 g of carbon black is filled into a glass sample tube, which is used as a measurement sample. The spin-spin relaxation time (transverse relaxation time) T2 is measured under the following measurement conditions to obtain a T2 relaxation curve (free induction decay curve).

[0080] <Measurement conditions>

[0081] Measured nuclide: 1H, pulse mode: solid echo method (90°x-γ-90°y), 90°, pulse width: 2.7μs, measurement time: 2ms, waiting time: 500ms, accumulation times: 52 times, measurement temperature: 40℃, gain: 90

[0082] In addition, the mass of carbon black is constant at 0.2 g, and the device function is also constant (gain (Gainn) = 90), so the signal intensity of the obtained T2 relaxation curve (free induction decay curve) increases or decreases in proportion to the 1H concentration of the measured object.

[0083] Next, the obtained autoinduction decay curve was fitted by the linear least square method using the fitting software (TD-NMR-A for Windows 7) attached to the pulsed nuclear magnetic resonance apparatus, thereby obtaining an approximate curve represented by the following formula f(t).

[0084]

[0085] Wherein, T2(1) is the relaxation time of the component with a short relaxation time, T2(2) is the relaxation time of the component with a long relaxation time, A(1) is the signal intensity of the component with a short relaxation time at t=0, and A(2) is the signal intensity of the component with a long relaxation time at t=0.

[0086] Finally, by dividing the signal intensity A(1) by the mass (g) of the measured sample, the hydrogen content of the carbon black can be obtained.

[0087] In addition, depending on the time constant, the signal intensity A(1) can be determined as hydrogen atoms on the carbon black surface, and the signal intensity A(2) can be determined as water adsorbed on the carbon black surface, liquid polycyclic aromatic hydrocarbon compounds, etc. The signal intensity A(1) is equivalent to the "first signal" in the present invention, and the signal intensity A(2) is equivalent to the "second signal" in the present invention.

[0088] In addition, the carbon black used as the reference in the measurement of the hydrogen content is Seast 9 (trade name) manufactured by Tokai Carbon Co., Ltd., and its hydrogen content is 114 / g. The hydrogen content of the carbon black used in the present invention is determined by adjusting the measurement conditions that affect the signal intensity so that the hydrogen content of Seast 9 becomes 114 / g.

[0089] In the Raman spectrum of carbon black measured with a laser Raman spectrometer at an excitation wavelength of 532 nm, the -1 The half-peak width ΔD of the Raman scattering peak appearing in the range of 260 to 290 cm -1 ΔD represents the disorder of the crystal structure on the surface of carbon black, that is, the crystallinity. When ΔD is within the above range, the dispersibility of carbon black is high, the roll processability of the acrylic rubber composition can be excellent, and the tensile strength of the obtained rubber cross-linked product can be excellent.

[0090] ΔD can be measured by the following method. First, carbon black is measured by laser Raman spectroscopy at an excitation wavelength of 532 nm to obtain a Raman spectrum. In the obtained Raman spectrum, the wavelengths between 1340 and 1360 cm -1 The measurement wavelength at the peak position in the range of is set as Dmax (cm -1), the detection position on the low wavelength side having a detection intensity half of the peak intensity of Dmax is set as D50 (cm -1 ). ΔD can be calculated by the following formula (1).

[0091]

[0092] In the measurement by Raman spectroscopy, the carbon black used as a standard was Seast G-SO (trade name) manufactured by Tokai Carbon Co., Ltd., and the ΔD value thereof was 249 cm -1 The ΔD of the carbon black used in the present invention is such that the ΔD of Seast G-SO is 249 cm -1 It is obtained by adjusting the measurement conditions that affect ΔD in a manner.

[0093] The content of carbon black in the acrylic rubber composition is not particularly limited, but is preferably 5 to 100 parts by weight, more preferably 10 to 70, and even more preferably 50 to 70, based on 100 parts by weight of the rubber component containing the acrylic rubber.

[0094] The acrylic rubber composition of the present invention contains carbon black having the above-mentioned properties. An acrylic rubber composition containing an acrylic rubber having a glass transition temperature of -29°C or less and carbon black generally used in acrylic rubber tends to have poor roll processability. On the other hand, in the present invention, by using the above-mentioned carbon black, even when combined with an acrylic rubber having a glass transition temperature of -29°C or less, the roll processability of the acrylic rubber composition can be made excellent, and the tensile strength of the obtained rubber cross-linked product can be made excellent.

[0095] The acrylic rubber composition of the present invention may contain other reinforcing fillers and non-reinforcing fillers in addition to the above-mentioned carbon black.

[0096] As reinforcing fillers, for example, carbon black such as furnace black, acetylene black, pyrolytic carbon black, channel carbon black, and graphite; silicon dioxide such as wet silica, dry silica, and colloidal silica, etc. In addition, as non-reinforcing fillers, clay such as quartz powder and diatomaceous earth, zinc oxide, basic magnesium carbonate, activated calcium carbonate, magnesium silicate, aluminum silicate, titanium dioxide, talc, aluminum sulfate, calcium sulfate, and barium sulfate, etc., can be cited. In addition, the carbon black used as a reinforcing filler is different from the carbon black used in the present invention, and its nitrogen adsorption specific surface area / iodine adsorption amount, nitrogen adsorption specific surface area, iodine adsorption amount, DBP absorption amount, hydrogen amount obtained by NMR, and half-peak width ΔD of the Raman scattering peak do not meet the above requirements.

[0097] Carbon black and other fillers can be used alone or in combination of two or more. The content of carbon black and other fillers in the acrylic rubber composition of the present invention is not particularly limited, and is preferably 1 to 200 parts by weight, more preferably 10 to 150 parts by weight, and further preferably 20 to 100 parts by weight relative to 100 parts by weight of the rubber component of the acrylic rubber composition.

[0098] The Mooney viscosity (ML1+4, 100°C) of the acrylic rubber composition of the present invention is preferably 10 to 80, more preferably 20 to 70, and even more preferably 30 to 60. When the Mooney viscosity of the acrylic rubber composition is within the above range, the roll processability and strength characteristics of the acrylic rubber composition can be well balanced.

[0099] The acrylic rubber composition of the present invention preferably further contains a plasticizer. The plasticizer is not particularly limited as long as it is a plasticizer commonly used as a rubber plasticizer, and is preferably an ester compound of a dicarboxylic acid and an ether bond-containing alcohol. Examples of such plasticizers include adipic acid ether ester-based plasticizers and the like.

[0100] The content of the plasticizer in the acrylic rubber composition is preferably 0 to 40 parts by weight, more preferably 1 to 30 parts by weight, and even more preferably 3 to 20 parts by weight relative to 100 parts by weight of the rubber component containing the acrylic rubber. By setting the content of the plasticizer in the acrylic rubber composition within the above range, the obtained rubber cross-linked product can have excellent cold resistance.

[0101] The acrylic rubber composition of the present invention preferably further contains a crosslinking agent. As the crosslinking agent, there is no particular limitation, and conventionally known crosslinking agents such as polyamine compounds such as diamine compounds and carbonates thereof; sulfur; sulfur donors; triazine thiol compounds; polycyclic epoxy compounds; organic carboxylic acid ammonium salts; organic peroxides; dithiocarbamic acid metal salts; polycarboxylic acids; quaternary onium salts; imidazole compounds; isocyanuric acid compounds, etc. can be used. These crosslinking agents can be used alone or in combination of two or more. Among these, polyamine compounds and carbonates thereof are preferably used.

[0102] The content of the crosslinking agent in the acrylic rubber composition is preferably 0 to 5 parts by weight, more preferably 0.1 to 3 parts by weight, and even more preferably 0.2 to 1 part by weight relative to 100 parts by weight of the rubber component containing the acrylic rubber. By making the content of the crosslinking agent within the above range, the tensile strength of the obtained rubber cross-linked product can be made even better.

[0103] The polyamine compound and its carbonate are not particularly limited, but preferably are polyamine compounds and their carbonates having 4 to 30 carbon atoms. Examples of such polyamine compounds and their carbonates include aliphatic polyamine compounds and their carbonates, and aromatic polyamine compounds.

[0104] The aliphatic polyamine compound and its carbonate are not particularly limited, and examples thereof include hexamethylenediamine, hexamethylenediamine carbamate, and N,N′-dicinnamylidene-1,6-hexanediamine, etc. Among these, hexamethylenediamine carbamate is preferred.

[0105] The aromatic polyamine compound is not particularly limited, and examples thereof include 4,4'-methylenedianiline, p-phenylenediamine, m-phenylenediamine, 4,4'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, 4,4'-(m-phenylenediisopropylidene)diphenylamine, 4,4'-(p-phenylenediisopropylidene)diphenylamine, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, 4,4'-diaminobenzanilide, 4,4'-bis(4-aminophenoxy)biphenyl, m-phenylenediamine, p-phenylenediamine, and 1,3,5-phenyltriamine. Among these, 2,2'-bis[4-(4-aminophenoxy)phenyl]propane is preferred.

[0106] In addition, the acrylic rubber composition of the present invention preferably also contains a crosslinking accelerator. As a crosslinking accelerator, there is no particular limitation. When the acrylic rubber has a carboxyl group as a crosslinking group and the crosslinking agent is a polyamine compound or its carbonate, guanidine compounds, diazabicycloolefin compounds, imidazole compounds, quaternary onium salts, tertiary phosphine compounds, aliphatic mono-secondary amine compounds and aliphatic mono-tertiary amine compounds can be used. Among these, guanidine compounds, diazabicycloolefin compounds and aliphatic mono-secondary amine compounds are preferred, and guanidine compounds and diazabicycloolefin compounds are particularly preferred. These basic crosslinking accelerators can be used alone or in combination of two or more.

[0107] Specific examples of guanidine compounds include 1,3-di-o-tolylguanidine and 1,3-diphenylguanidine. Specific examples of diazabicycloolefin compounds include 1,8-diazabicyclo[5.4.0]undec-7-ene and 1,5-diazabicyclo[4.3.0]non-5-ene. Specific examples of imidazole compounds include 2-methylimidazole and 2-phenylimidazole. Specific examples of quaternary onium salts include tetra-n-butylammonium bromide and octadecyltri-n-butylammonium bromide. Specific examples of tertiary phosphine compounds include triphenylphosphine and tri-p-tolylphosphine.

[0108] The aliphatic mono-secondary amine compound is a compound in which two hydrogen atoms of ammonia are replaced by aliphatic hydrocarbon groups. The aliphatic hydrocarbon group replacing the hydrogen atom is preferably an aliphatic hydrocarbon group having 1 to 30 carbon atoms. Specific examples of the aliphatic mono-secondary amine compound include dimethylamine, diethylamine, dipropylamine, diallylamine, diisopropylamine, di-n-butylamine, di-tert-butylamine, di-sec-butylamine, dihexylamine, diheptylamine, dioctylamine, dinonylamine, didecylamine, diundecylamine, didodecylamine, ditridecylamine, ditetradecylamine, dipentadecylamine, dihexadecylamine, di-2-ethylhexylamine, and dioctadecylamine.

[0109] The aliphatic mono-tertiary amine compound is a compound in which all three hydrogen atoms of ammonia are replaced by aliphatic hydrocarbon groups. The aliphatic hydrocarbon group replacing the hydrogen atom is preferably an aliphatic hydrocarbon group having 1 to 30 carbon atoms. Specific examples of the aliphatic mono-tertiary amine compound include trimethylamine, triethylamine, tripropylamine, triallylamine, triisopropylamine, tri-n-butylamine, tri-tert-butylamine, tri-sec-butylamine, trihexylamine, triheptylamine, trioctylamine, trinonylamine, tridecylamine, triundecylamine, and tridodecylamine.

[0110] The content of the crosslinking accelerator in the acrylic rubber composition of the present invention is preferably 0.1 to 10 parts by weight, more preferably 0.5 to 7.5 parts by weight, and particularly preferably 1 to 5 parts by weight relative to 100 parts by weight of the rubber component containing the acrylic rubber. By making the content of the crosslinking accelerator within the above range, the tensile strength and compression set resistance of the obtained rubber crosslinked product can be further improved.

[0111] The acrylic rubber composition of the present invention may contain an antioxidant as required. The antioxidant is not particularly limited, and examples thereof include: the above-mentioned phenol antioxidants; phosphite antioxidants such as tris(nonylphenyl)phosphite, diphenylisodecylphosphite, and tetraphenyldipropylene glycol diphosphite; thioester antioxidants such as dilauryl thiodipropionate; amine antioxidants such as phenyl-α-naphthylamine, phenyl-β-naphthylamine, p-(p-toluenesulfonamide)diphenylamine, 4,4'-bis(α,α-dimethylbenzyl)diphenylamine, N,N-diphenyl-p-phenylenediamine, N-isopropyl-N'-phenyl-p-phenylenediamine, and butyraldehyde-aniline polycondensate; imidazole antioxidants such as 2-mercaptobenzimidazole; quinoline antioxidants such as 6-ethoxy-2,2,4-trimethyl-1,2-dihydroquinoline; hydroquinone antioxidants such as 2,5-di(tert-amyl)hydroquinone, and the like.

[0112] The antioxidant can be used alone or in combination of two or more. The content of the antioxidant in the rubber composition of the present invention is not particularly limited, but is preferably 0.01 to 15 parts by weight, more preferably 0.05 to 10 parts by weight, and even more preferably 0.1 to 5 parts by weight, relative to 100 parts by weight of the rubber component containing the copolymer rubber of the present invention.

[0113] In addition, the acrylic rubber composition of the present invention can be mixed with compounding agents commonly used in the field of rubber processing in addition to the above-mentioned components. Examples of such compounding agents include: light stabilizers; anti-scorching agents; processing aids; adhesives; lubricants; lubricants; flame retardants; mildew inhibitors; antistatic agents; colorants; crosslinking delay agents, etc. The amount of these compounding agents is not particularly limited as long as it does not hinder the purpose and effect of the present invention, and can be appropriately mixed in an amount corresponding to the purpose of mixing.

[0114] The acrylic rubber composition of the present invention can be prepared by adding a crosslinking agent and other various compounding ingredients used as needed to a rubber component containing acrylic rubber, mixing and kneading them using an open roll, a Banbury mixer, various kneading machines, etc., and then further kneading them using a kneading roll.

[0115] The order of mixing the components is not particularly limited. It is preferred that the components that are not easily reacted or decomposed by heat are fully mixed, and then the crosslinking agent or the like that is a component that is easily reacted or decomposed by heat is mixed in a short time at a temperature that does not react or decompose.

[0116] <Rubber cross-linked products>

[0117] The cross-linked rubber of the present invention is obtained by cross-linking the acrylic rubber composition of the present invention.

[0118] The cross-linked rubber of the present invention can be manufactured as follows: using the acrylic rubber composition of the present invention, it is molded by a molding machine corresponding to the desired shape, such as an extruder, an injection molding machine, a compressor, and a roller, and heated, thereby performing a cross-linking reaction and fixing the shape in the form of a cross-linked rubber. In this case, cross-linking can be performed after pre-molding, or cross-linking can be performed simultaneously with molding. The molding temperature is generally 10 to 200°C, preferably 25 to 120°C. The cross-linking temperature is generally 130 to 220°C, preferably 150 to 190°C, and the cross-linking time is generally 2 minutes to 10 hours, preferably 3 minutes to 5 hours. As a heating method, a method used in the cross-linking of rubber, such as press heating, steam heating, oven heating, and hot air heating, can be appropriately selected.

[0119] In addition, the cross-linked rubber of the present invention may be further heated to perform secondary cross-linking, depending on the shape and size of the cross-linked rubber. The secondary cross-linking varies depending on the heating method, cross-linking temperature, shape, etc., and is preferably performed for 1 to 48 hours. The heating method and heating temperature may be appropriately selected.

[0120] Moreover, the rubber cross-linked product of the present invention thus obtained can be suitably used as: sealing materials such as O-rings, packings, diaphragms, oil seals, shaft seals, bearing seals, mechanical seals, wellhead seals, seals for electrical / electronic equipment, seals for air compression equipment, etc.; cylinder head gaskets installed at the connection between the cylinder block and the cylinder head, rocker cover gaskets installed at the connection between the rocker cover and the cylinder head, oil pan gaskets installed at the connection between the oil pan and the cylinder head or the transmission case, gaskets for fuel cell spacers installed between a pair of shells that clamp unit cells having a positive electrode, an electrolyte plate and a negative electrode, gaskets for top covers of hard disk drives, and various other gaskets; cushioning materials, shockproof materials; wire covering materials; industrial belts; pipes / hoses; sheets, etc.

[0121] The rubber cross-linked product of the present invention can be suitably used as an extrusion-molded product and a cross-linked product for use in automobiles, for example, various hoses such as fuel hoses, filler neck hoses, exhaust hoses, steam hoses, and oil hoses for fuel tanks, air hoses such as turbo air hoses and transmission control hoses, radiator hoses, heater hoses, brake hoses, and air conditioning hoses.

[0122] <<Second embodiment>>

[0123] Next, the acrylic rubber composition according to the second embodiment of the present invention will be described.

[0124] The acrylic rubber composition of the second embodiment contains: acrylic rubber; carbon black, wherein the nitrogen adsorption specific surface area / iodine adsorption amount is 1.00×10 3 m 2 / g or more and the nitrogen adsorption specific surface area is 25m 2 / g or more; and a plasticizer, wherein the content of the plasticizer is 3 parts by weight or more relative to 100 parts by weight of the rubber component containing the acrylic rubber.

[0125] The monomer units constituting the acrylic rubber used in the second embodiment may be the same as those constituting the acrylic rubber in the first embodiment. The acrylic rubber used in the second embodiment may be obtained by polymerizing the monomers used in the acrylic rubber in the first embodiment by emulsion polymerization or the like.

[0126] The glass transition temperature of the acrylic rubber used in the second embodiment is not particularly limited, but is preferably -10° C. to -40° C. When the glass transition temperature (Tg) is within the above range, the balance between heat resistance and cold resistance of the acrylic rubber can be further improved.

[0127] The acrylic rubber composition in the second embodiment is similar to that in the first embodiment and contains a nitrogen adsorption specific surface area / iodine adsorption amount of 1.00×10 3 m 2 / g or more and the nitrogen adsorption specific surface area is 25m 2 / g or more carbon black. An acrylic rubber composition containing acrylic rubber, carbon black generally used in acrylic rubber, and 3 parts by weight or more of a plasticizer relative to 100 parts by weight of a rubber component tends to have poor roll processability. On the other hand, in the present invention, by using the above-mentioned carbon black, the roll processability of the acrylic rubber composition containing 3 parts by weight or more of a plasticizer can be improved, and the tensile strength of the obtained rubber cross-linked product can be improved.

[0128] The carbon black used in the second embodiment is the same as the carbon black used in the first embodiment, and preferably the nitrogen adsorption specific surface area / iodine adsorption amount, nitrogen adsorption specific surface area, iodine adsorption amount, DBP absorption amount, hydrogen amount determined by NMR and half-peak width ΔD of the Raman scattering peak are within the specified ranges.

[0129] That is, the nitrogen adsorption specific surface area / iodine adsorption amount of carbon black is preferably 1.10×10 3 ~1.50×10 3 m 2 / g, and the nitrogen adsorption specific surface area is preferably 25 to 60 m 2 / g, and the iodine adsorption amount is preferably 17 to 60 mg / g. In addition, the DBP absorption of carbon black is preferably 90 to 180 cm 3 / 100g. In addition, the amount of hydrogen determined by NMR is preferably 150 to 250 / g. In addition, in the Raman spectrum obtained by measuring with an excitation wavelength of 532nm using a laser Raman spectrometer, it is preferred that the peaks at 1340 to 1360cm -1 The half-peak width ΔD of the Raman scattering peak in the range of 260 to 290 cm -1 .

[0130] The content of carbon black in the acrylic rubber composition is preferably 5 to 100 parts by weight, more preferably 10 to 70 parts by weight, and even more preferably 50 to 70 parts by weight.

[0131] The content of the plasticizer in the acrylic rubber composition in the second embodiment is 3 parts by weight or more, preferably 5 parts by weight or more, and more preferably 7 parts by weight or more, relative to 100 parts by weight of the rubber component containing the acrylic rubber. The upper limit of the content of the plasticizer in the acrylic rubber composition is not particularly limited, but is preferably 30 parts by weight or less, and more preferably 20 parts by weight or less. By setting the content of the plasticizer in the acrylic rubber composition within the above range, the obtained rubber cross-linked product can have excellent cold resistance.

[0132] As the plasticizer used in the second embodiment, the same plasticizers as those used in the first embodiment can be mentioned.

[0133] The acrylic rubber composition in the second embodiment may contain the crosslinking agent, crosslinking accelerator, antioxidant, and other commonly used compounding agents described in the first embodiment in addition to the above-mentioned components. The acrylic rubber composition in the second embodiment is prepared by mixing a crosslinking agent and other various compounding agents used as needed with a rubber component containing acrylic rubber, mixing and kneading them using an open roll, a Banbury mixer, various kneading machines, etc., and then further kneading them using a kneading roll.

[0134] The rubber cross-linked product in the second embodiment can be obtained by the same method as described in the first embodiment using the above-mentioned acrylic rubber composition.

[0135] Example

[0136] Hereinafter, the present invention will be described in detail by way of examples, but the present invention is not limited to these examples. In addition, unless otherwise specified, the following "parts" are weight references. In addition, various physical properties are measured as follows.

[0137] <Glass transition temperature>

[0138] The glass transition temperature of the acrylic rubber was measured using a differential scanning calorimetry (DSC).

[0139] <Roller processability>

[0140] Roll processability was determined based on the operability when the acrylic rubber composition was wound around a roll at a temperature of 50° C. using a kneading machine (8-inch roll).

[0141] ○: Roller operation can be performed without any problems

[0142] △: Strong adhesion to the roll, but roll operation is possible

[0143] ×: Very strong adhesion to the roller, difficult to operate the roller

[0144] <Normal physical properties (tensile strength)>

[0145] The rubber composition was placed in a mold of 15 cm in length, 15 cm in width, and 0.2 cm in depth, and pressed at 170°C for 20 minutes while being pressed at a pressing pressure of 10 MPa to obtain a sheet-like cross-linked rubber product. The obtained cross-linked rubber product was then transferred to a Gill oven and subjected to secondary cross-linking at 170°C for 4 hours. The obtained sheet-like cross-linked rubber product was punched out with a JIS No. 3 dumbbell to prepare a test piece. The obtained test piece was then used to measure the tensile strength of the cross-linked rubber product in accordance with JIS K6251:2017.

[0146] <Cold resistance test>

[0147] The acrylic rubber composition was placed in a mold of 15 cm in length, 15 cm in width and 0.2 cm in depth, and pressed at 170°C for 20 minutes while being pressurized to form a sheet-like cross-linked product, and then secondary cross-linked at 170°C for 4 hours to obtain a sheet-like rubber cross-linked product. The obtained sheet-like cross-linked product was used to determine the cold resistance of the rubber cross-linked product by the TR test (low temperature elastic recovery test) in accordance with JIS K6261-4:2017. Specifically, the test piece after elongation was frozen and the temperature was continuously raised, thereby determining the recovery of the test piece after elongation, and determining the temperature TR10 when the length of the test piece shrinks (recovers) 10% by heating. The lower the temperature TR10, the better the cold resistance can be judged.

[0148] <Example 1>

[0149] (Preparation of acrylic rubber composition)

[0150] 60 parts of MAF (Medium Abrasion Furance) carbon (carbon black), 5 parts of polyether ester plasticizer (trade name "ADK CIZER RS-735", manufactured by Adecco Co., Ltd.), 2 parts of stearic acid, 0.5 parts of crosslinking agent (trade name "VC-1", manufactured by Chemours), and 2 parts of crosslinking aid (trade name "RHENOGRAN XLA-60 (GE2014)", manufactured by Rhein Chemie, DBU 60% (including the portion of dialkyl diphosphonic acid zinc salt) were mixed with 100 parts of carboxylic acid acrylic rubber (trade name "NipolAR14", manufactured by Nippon Zeon Co., Ltd.) using a kneader, and kneaded with a roll to obtain an acrylic rubber composition. The obtained acrylic rubber composition was used to measure roll processability, and the tensile strength and cold resistance of the rubber cross-linked product were measured. The results are shown in Table 1. In addition, as carbon black, a carbon black having a nitrogen adsorption specific surface area / iodine adsorption amount of 1.3 was used. 3 ×103m2 / g, nitrogen adsorption specific surface area is 53m 2 / g, iodine adsorption capacity is 40mg / g, DBP absorption capacity is 120cm 3 / 100g, the amount of hydrogen measured by the above method is 150 to 250 / g, and the half-peak width ΔD of the Raman scattering peak measured by the above method is 260 to 290 cm -1 of carbon black.

[0151] <Example 2>

[0152] An acrylic rubber composition was obtained in the same manner as in Example 1, except that 100 parts of chlorinated acrylic rubber (trade name "NipolAR74X", manufactured by Nippon Zeon Co., Ltd.) was used instead of 100 parts of carboxylic acid acrylic rubber, and 0.3 parts of sulfur, 3 parts of a crosslinking aid (trade name "NONSOUL SN-1", manufactured by NOF Corporation) and 0.5 parts of a crosslinking aid (trade name "NONSOUL SK-1", manufactured by NOF Corporation) were used instead of 0.5 parts of the crosslinking agent (VC-1) and 2 parts of the crosslinking aid (XLA-60). The results are shown in Table 1.

[0153] <Example 3>

[0154] An acrylic rubber composition was obtained in the same manner as in Example 1, except that 100 parts of carboxylic acid acrylic rubber (trade name "Nipol AR12", manufactured by Nippon Zeon Co., Ltd.) was used instead of 100 parts of carboxylic acid acrylic rubber (Nipol AR14) and the amount of carbon black was changed to 65 parts, and the evaluation was performed in the same manner. The results are shown in Table 1.

[0155] <Example 4>

[0156] An acrylic rubber composition was obtained in the same manner as in Example 2 except that 100 parts of chlorinated acrylic rubber (trade name "Nipol AR71", manufactured by Nippon Zeon Co., Ltd.) was used instead of 100 parts of chlorinated acrylic rubber (Nipol AR12) and the amount of plasticizer was changed to 15 parts, and the evaluation was performed in the same manner. The results are shown in Table 1.

[0157] <Example 5>

[0158] An acrylic rubber composition was obtained in the same manner as in Example 2, and was evaluated in the same manner, except that 100 parts of epoxy acrylic rubber (trade name "Nipol AR42W", manufactured by Nippon Zeon Co., Ltd.) was used instead of 100 parts of chlorine acrylic rubber, the amount of carbon black was 65 parts, and the amount of plasticizer was 10 parts. The results are shown in Table 1.

[0159] <Example 6>

[0160] The acrylic rubber composition was obtained in the same manner as in Example 1 except that no plasticizer was used, and the evaluation was performed in the same manner.

[0161] <Comparative Examples 1-2, 5>

[0162] Except for changing the types and amounts of the acrylic rubber and compounding ingredients as shown in Table 1, an acrylic rubber composition was obtained in the same manner as in Example 1, and the evaluation was performed in the same manner.

[0163] <Comparative Example 3>

[0164] An acrylic rubber composition was obtained in the same manner as in Example 1 except that 60 parts of carbon black (trade name "N330", manufactured by Cabot Japan Ltd.) was used instead of 60 parts of the carbon black used in Example 1, and evaluation was performed in the same manner.

[0165] <Comparative Example 4>

[0166] An acrylic rubber composition was obtained in the same manner as in Example 1 except that 60 parts of carbon black (trade name "N550", manufactured by Cabot Japan Ltd.) was used instead of 60 parts of the carbon black used in Example 1, and evaluation was performed in the same manner.

[0167] [Table 1]

[0168]

[0169] As shown in Table 1, the acrylic rubber containing a glass transition temperature of -29°C or less and a nitrogen adsorption specific surface area / iodine adsorption amount of 1.00×10 3 m 2 / g or more and the nitrogen adsorption specific surface area is 25m 2 The acrylic rubber composition containing carbon black of 1.00 × 10 / g or more has excellent roll processability and can form a rubber cross-linked product with excellent cold resistance and tensile strength (Examples 1-2 and 6). 3 m 2 / g or more and the nitrogen adsorption specific surface area is 25m 2 An acrylic rubber composition containing carbon black in an amount of at least 1 part by weight and 3 parts by weight or more of a plasticizer per 100 parts by weight of the rubber component has excellent roll processability and can form a rubber cross-linked product having excellent cold resistance and tensile strength (Examples 3-5).

[0170] On the other hand, even if the acrylic rubber contains a nitrogen adsorption specific surface area / iodine adsorption amount of 1.00×10 3 m 2 / g or more and the nitrogen adsorption specific surface area is 25m 2 When the acrylic rubber composition containing carbon black of 0.1% to 0.2% by weight or more and the content of the plasticizer is less than 3 parts by weight, the obtained rubber cross-linked product has poor cold resistance (Comparative Examples 1-2 and 5).

[0171] In addition, the nitrogen adsorption specific surface area / iodine adsorption amount was less than 1.00×10 3 m 2 / g of carbon black had poor roll processability (Comparative Examples 3-4), and the tensile strength of the rubber cross-linked product was poor (Comparative Example 4).

Claims

1. An acrylic rubber composition comprising: Acrylic rubber having a glass transition temperature of below -29°C; and Carbon black, its nitrogen adsorption specific surface area / iodine adsorption amount is 1.00×10 3 m 2 / g or more and the nitrogen adsorption specific surface area is 25m 2 / g or above.

2. An acrylic rubber composition comprising: Acrylic rubber; Carbon black, its nitrogen adsorption specific surface area / iodine adsorption amount is 1.00×10 3 m 2 / g or more and the nitrogen adsorption specific surface area is 25m 2 / g or more; and Plasticizers, The content of the plasticizer is 3 parts by weight or more based on 100 parts by weight of the rubber component including the acrylic rubber.

3. The acrylic rubber composition according to claim 1, wherein The acrylic rubber composition further contains a plasticizer.

4. The acrylic rubber composition according to any one of claims 1 to 3, wherein The nitrogen adsorption specific surface area of ​​the carbon black is 25 to 60 m 2 / g, The nitrogen adsorption specific surface area / iodine adsorption amount of the carbon black is 1.10×10 3 ~1.50×10 3 m 2 / g.

5. The acrylic rubber composition according to any one of claims 1 to 4, wherein The DBP absorption of the carbon black is 90 to 180 cm 3 / 100g.

6. The acrylic rubber composition according to any one of claims 1 to 5, wherein In the carbon black, when the nuclear magnetic resonance signal of the spin-spin relaxation process observed by the solid echo method is represented by the sum of a first signal and a second signal having a time constant larger than that of the first signal, the amount of hydrogen represented by the signal intensity per unit mass at time 0 of the first signal is 150 to 250 / g.

7. The acrylic rubber composition according to any one of claims 1 to 6, wherein In the carbon black, when the excitation wavelength is set to 532 nm, the -1 The half-peak width ΔD of the Raman scattering peak in the range of 260 to 290 cm -1 .

8. The acrylic rubber composition according to claim 1 or 2, wherein The nitrogen adsorption specific surface area of ​​the carbon black is 25 to 60 m 2 / g, The nitrogen adsorption specific surface area / iodine adsorption amount of the carbon black is 1.10×10 3 ~1.50×10 3 m 2 / g, The DBP absorption of the carbon black is 90 to 180 cm 3 / 100g, In the carbon black, when a nuclear magnetic resonance signal of a spin-spin relaxation process observed by a solid echo method is represented by a sum of a first signal and a second signal having a larger time constant than the first signal, the amount of hydrogen represented by the signal intensity per unit mass at time 0 of the first signal is 150 to 250 / g, In the carbon black, when the excitation wavelength is set to 532 nm, the -1 The half-peak width ΔD of the Raman scattering peak in the range of 260 to 290 cm -1 . 9 . A rubber cross-linked product obtained by cross-linking the acrylic rubber composition according to claim 1 with an amine compound.

Citation Information

Patent Citations

  • Acrylic rubber composition for heat-resistant hose, heat-resistant hose using the same, and method for production of heat-resistant hose

    JP2016150525A